VALUE OF CONVENTIONAL MAGNETIC RESONANCE IN DIAGNOSIS OF ROTATOR CUFF TEAR (Vietnam Journal of Community Medicine, 2021)
Objective: To study on the value of conventional magnetic resonance imaging in the diagnosis of rotator cuff tear in comparison with surgery.Subjects and research methods: Cross-sectional descriptive study on 69 patients with rotator cuff lesions undergoing magnetic resonance imaging at Hanoi Medical University Hospital Departmentof Diagnostic Imaging, all patients have surgery after that.Results: Among the number of patients operated, the highest proportion was the complete tendon rupture group (accounting for 60.9%), followed by the full-thickness tear group (14.5%) and thearticular-surface tear group (14.5%). , the groups of synovial-surface tear, intrasubstance tear, simple tendinopathy accounted for the least percentage. Regarding post-operative comparison: For completetendon tear, the sensitivity of magnetic resonance is 100%, specificity is 95.7%; in full-thickness tear, the sensitivity and specificity of magnetic resonance were 100% and 98.7%. The sensitivityof conventional magnetic resonance in the diagnosis of partial tear such as articular-surface tears, synovial-surface tear is 50-60% and specificity is 74.9-98.7%.Conclusion: Routine magnetic resonance imaging is a valuable method in diagnosing rotator cuff tears. The sensitivity and specificity of magnetic resonance are high in the diagnosis of major tendon tears (complete and full-thickness tears) than in cases of partial tear (articular or synovial surface tear).
Keywords: Magnetic resonance imaging, rotator cuff tear, complete tendon tear, full-thickness tear, articular- surface tear, synovial-surface tear